Five‐country manikin study found that neonatologists preferred using the LISAcath rather than the Angiocath for less invasive surfactant administration. (25th January 2018) - Fabbri, Laura; Klebermass‐Schrehof, Katrin; Aguar, Marta; Harrison, Catherine; Gulczyńska, Ewa; Santoro, Debora; Di Castri, Marco; Rigo, Vincent
Abstract: Aim: Less invasive surfactant administration (LISA) has been shown to decrease the risk of death and bronchopulmonary dysplasia in preterm neonates. The LISAcath is the first catheter to be specifically developed for LISA, and we compared the clinical impressions of neonatologists using the LISAcath and the commonly used Angiocath in a simulated setting. Methods: This was a multinational, multicentre study, conducted in October 2016, which involved 39 neonatologists who were recruited by employees of the sponsor from large, well‐recognised neonatal intensive care units across Europe. LISA was not the standard of care in these units in Austria, Belgium, Poland, Spain and the United Kingdom at the time of the study. After training, participants simulated LISA on a neonatal manikin, once with the LISAcath and once with Angiocath, then answered a 10‐item questionnaire. Results: The responses to nine of 10 questions showed that 67‐95% of the respondents preferred the LISAcath to the Angiocath, with most of the remainder indicating no preference. The only exception was the luer connection question, with two‐thirds expressing no preference. The LISAcath was considered potentially safer by 33 of 39 participants, with no votes for the Angiocath. Conclusion: Overall, neonatologists preferred using the LISAcath rather than the Angiocath on a neonatal manikin.